Ernest Bloch, Richard Wagner, and the Myth of Racial Essentialism - Klaus, Aaron (Studies in Christian-Jewish Relations, 2018)
Composer Ernest Bloch’s Jewish identity is ironically rooted in the notoriously anti-Semitic writings of Richard Wagner. Rather than an indication of self-loathing, Bloch’s assimilation of Wagner's ideas into his own thinking exemplifies the seductiveness of racial essentialist thought in the late nineteenth and early twentieth centuries. An examination of the effects of racial essentialism and Jewish assimilation in post-Emancipation Europe puts Bloch’s identity as a Jewish composer in context. Next, a biographical sketch of Bloch’s life sheds light on how he grappled with Judaism in his music. Finally, a discussion of Bloch’s relationship with Judaism shows the danger of defining Jewish music in racial terms.